Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan(Studi Kasus pada Warung Spesial Sambal Cabang UMS) - Suprapto, Riki Hadi; , Basworo Dibyo, S.E, M.Si (2016)
The purpose of this study was to analyze the influence know the quality of service to customer satisfaction in Public Eating Branch Special Sambal UMS. The study was conducted by distributing questionnaires to customers Public Eating Branch Special Sambal UMS. The number of customers who seek respondents were 100 respondents drawn from the customers who come to the Public Eating Branch Special Sambal UMS. The research method using multiple regression analysis. Based on the survey results revealed that the results of multiple regression analysis with the following equation: Y = -2,076 + 0,265 X1 + 0,213 X2 + 0,171 X3 + 0,235 X4+ 0,610 X5. T test results showed that variable responsiveness is the variable that gives a dominant influence on consumer satisfaction. It can be seen from the t¬hitung variable responsiveness (7.243), higher than other variables tcount tangibles (3.970), assurance (3.107), empathy (3,050) and reliability (2.512). This means that if responsiveness in providing services cause consumers to feel satisfied. The result of the coefficient of determination (R2) obtained a value of R2 = 0.772, meaning that 77.2% of the variation is influenced by tangible customer satisfaction, reliability, assurance, empathy and responsiveness, while the remaining 22.8% is influenced by other variables not examined. F test results received grades of F> Ftabel (63.661> 2.29) at the 5% significance level. This means that means there is significant influence from tangible, reliability, assurance, empathy and responsiveness, together on customer satisfaction. It concluded that tangible, reliability, assurance, empathy, and responsiveness together or partially positive effect on customer satisfaction in Public Eating Branch Special Sambal UMS. Keywords: customer satisfaction, tangibles, reliability, responsiveness, assurance, empathy